Waste to value added product: Vermicomposting of sugar cane bagasse and leaves using African nightcrawlers (Eudrillus Eugeniae) - Krishnan, S.; Shahul Hamid, F.; Uche, E.C.; Mahamad Rasid, M.H. (2011)
The high volume of waste dumped per day leads to serious environmental issues. Among the issues is the generation of methane via anaerobic degradation of waste that contributes towards global warming. There are numerous options in minimizing organic waste disposed into landfills. This includes composting, recycling and vermicomposting. This study is aimed to investigate the possibility of treating sugar cane leaves and bagasse via vermicomposting by using Eudrillus eugeniae (African night crawler) worms. Therefore, the study compared degradation potential between sugar cane bagasse and leaves. Each of sugar cane bagasse and leaves were mixed with soil at selected waste to soil ratios namely 9:1, 7:3 and 1:1. Ten Eudrillus eugeniae with an average weight of 2.5±0.1g were added to each experimental set-up excluding the control. The result indicated that active burrowing potential of the worm into the soil was able to degrade the sugar cane leaves and sugar cane bagasse within 5 weeks and 6 weeks respectively. Also, the 1:1 treatment showed greater reduction of waste with increasing number of worms as compared with 9:1 treatment. Estimated degradation rate via vermicomposting was ±9.09 x 10-2 kg per day for the sugar cane leaves and 7.14 x 10-2 kg per day for sugar cane bagasse. The sugar cane bagasse and leaves are highly potential to degrade via vermicomposting but sugar cane leaves showed a better result to compost in a shorter duration compared to bagasse. Also, the vermicomposting of sugar cane bagasse and leaves using Eudrillus eugeniae in the ratio of 1:1 can be a better tool to divert the organic component from waste stream; to minimize the volume of waste disposal into landfill and produce the value added compost as the final product.